Analisis Dampak Merger dan Akuisisi Terhadap Kinerja Keuangan pada Perusahaan Non Keuangan Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2007 – 2014 - Lisa Laiman; Saarce Elsye Hatane (Business Accounting Review, 2017)
The purpose of this research is to analyze the difference of liquidity ratio, asset management ratio, debt management ratio, profitability ratio, market value ratio and firm size of non-financial sector companies listed on BEI before and after merger and acquisition. All non-financial sector companies listed on the Indonesia Stock Exchange and merged during the period 2010-2011. The sampling technique using purposive, with the sample number of non financial sector companies that comply the criteria is twelve companies. The analysis technique used paired sample t-test with SPSS software. The analysis result shows that there is no difference of current ration before and after merger. Similarly, the financial performance variables proxied with debt to equity ratio, return on assets, and return on equity all obtained results that is no difference in financial performance before and afeter merger. However, for asset turnover, price earnings ratio, and firm size shows that is different financial performance before and after merger.